Contribution of worldwork methodology for violence prevention and community recovery after mass violence: An example from Rwanda. (February 2017) - Audergon, Arlene; Audergon, Jean‐Claude
Abstract: In this article we propose that after violent conflict, and alongside tribunals and truth commissions, facilitated community dialogue is needed as part of a central strategy in transitional justice. Such facilitated dialogue supports community engagement in the task of recovery and prevention of mass violence and genocide. Facilitation is also needed wherever there are blocks to cooperation among international, government and non‐governmental organizations in the field. We illustrate the methodology of "worldwork", that is, Arnold Mindell's Process Oriented Psychology as applied to working with small and large groups, organizations and communities, and facilitating conflict resolution. Its methods make it possible to work in polarized communities and with volatile issues. We describe the initial stages of our work with survivors and perpetrators in Rwanda, and also draw upon our long‐term post‐conflict work in the Balkans. We highlight that the need to bear witness to collective trauma and to search for accountability links psychological, spiritual, social, and political awareness.